RANCANG BANGUN SISTEM KENDALI SUHU DAN KELEMBABAN DARI MINI GARDEN BUNGA KRISAN MENGGUNAKAN SMARTPHONE BERBASIS MIKROKONTROLER - Dananjaya, Bachtiar Putra; Sumariyah, Sumariyah (BERKALA FISIKA, 2021)
The  temperature  and  humidity  control  system  of  the  Krisan  Flower  Mini  Garden  has  been designed and implemented. The main components of this control systems were the NodeMCU 8266 microcontroller and smartphones that communicate using the internet of things (IoT). The system support components include the DHT 11 sensor module as a temperature and humidity sensor,  real time clock (RTC) module, liquid crystal display  (LCD) as a result viewer, relay board  module  and  pump.  The  microcontroller  read  and  processed  the  temperature  and humidity sensor output data in the form of a digital voltage signal. The measurement data were displayed on the LCD with an LED indicator and sent to the Telegram application. If the sensor output did not meet the needs of the Chrysanthemum flower, the microcontroller turned on the actuator to turn on the water pump and lights as irradiation. The system test was carried out in the Chrysanthemum Mini Garden by comparing the LCD reading with standard tools. The test results show a difference in temperature of about 0.2-3 oC and humidity of about 1-7%.